ETIKA KERJA ISLAM SEBAGAI VARIABEL INTERVENING ANTARA INTERNAL LOCUS OF CONTROL DENGAN ROLE CONFLICT KARYAWAN WANITA BERHIJAB - Dewi Nuraini (JURNAL MANAJERIAL, 2017)
The purpose of this study is to determine and explain the significance of the influence of Internal Locus of Control on Role Conflict with the ethics of Islamic work as intervening variable relationship. The type of research used in this research is explanatory research with quantitative research method. In this study using 3 (three) variables of internal locus of control as free variables, Islamic work ethics as intervening and role conflict variables as dependent variables. Where respondents in this study as many as 92 female respondents berhijab.This study uses statistical analysis regression path analysis method using SPSS 16 for windows and sobel test. To see the effect of mediation or intervening. Based on the results of the analysis show that the four hypotheses submitted accepted the truth, but the relationship between ethical work of Islam and positive role conflict in this study